Witch wraith [compact disc, unabridged] : the dark legacy of Shannara - Brooks, Terry (Brooks, Terry. Dark legacy of Shannara., 2013)
For centuries the Four Lands enjoyed freedom from its demon-haunted past, protected by magic-enhanced borders from the dark dimension known as the Forbidding and the profound evil imprisoned there. But now the unthinkable is happening. The ancient wards securing the barrier between order and mayhem have begun to erode, and generations of bloodthirsty, monstrous creatures are poised to spill forth, seeking revenge for what was done to them.